1997
DOI: 10.1002/(sici)1097-0207(19971030)40:20<3865::aid-nme246>3.0.co;2-c
|View full text |Cite
|
Sign up to set email alerts
|

Minimum time-step size for diffusion problem in FEM analysis

Abstract: In this paper oscillation of results arising from the use of a time-step size which is less than the minimum required is examined. The phenomenon is summarised to give two requirements that the solution of boundary problems has to satisfy. An approach to derive the minimum time-step size for various kinds of elements is developed. A theoretical verification is presented for the one-dimensional two-noded element case and a numerical examination of the criteria explored for the two-dimensional eight-noded elemen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
45
0

Year Published

1998
1998
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(47 citation statements)
references
References 9 publications
2
45
0
Order By: Relevance
“…The effect of time step size on the solution of transient heat transfer problems using the finite element method has been previously investigated in Thomas and Zhou (1997). However, it is important to note that the penalty formulation was unaffected at the tested time step of ∆x 2 100 ρcp k s (figure 7), suggesting that the Lagrange multiplier is more sensitive to this phenomenon.…”
Section: Phase 1d Problemmentioning
confidence: 95%
“…The effect of time step size on the solution of transient heat transfer problems using the finite element method has been previously investigated in Thomas and Zhou (1997). However, it is important to note that the penalty formulation was unaffected at the tested time step of ∆x 2 100 ρcp k s (figure 7), suggesting that the Lagrange multiplier is more sensitive to this phenomenon.…”
Section: Phase 1d Problemmentioning
confidence: 95%
“…Physically unrealisable results such as drying of soil near to an influx boundary can be obtained. To control numerical oscillation, Karthikeyan et al (2001) showed that a simple minimum time-step criteria, developed by Thomas and Zhou (1997) for heat diffusion problems with constant material properties, were also adequate for ensuring non-oscillatory solutions in realistic 2-D seepage flow regimes occurring within unsaturated porous media. The criteria were carefully verified using a range of highly non-linear geo-hydrologic properties commonly encountered in practice.…”
Section: Introductionmentioning
confidence: 99%
“…This is due to a violation of a discrete maximum principle. The principle further gives a The results are also verified in [57], where a minimum time step-size for the backward Euler method is derived. The phenomenon is different to the spatial oscillations which can be observed when using a reduced quadrature rule, as found in [39].…”
Section: Remarkmentioning
confidence: 73%
“…To avoid the loss of accuracy, a minimum time step criterion is derived. Also [57,62] investigate the effect of time step-size on the accuracy of time integration, in particular with regard to the minimum time step criterion. Kujawski and Wiberg [37] investigated a different class of time integration methods.…”
Section: Introductionmentioning
confidence: 99%